Diseño de un sistema de gestión y control operacional para una empresa que se dedica a la producción de banano ubicada en la provincia de Manabí - Ochoa Jara, Gina (2009)
The intentions and directions that takes an organization related to the control structure and process for its assets and activities that are consistent with the organizational strategic plan defined global Asset Management, where the success of an organization is significantly influenced by the performance of their assets, for this, the organization shall establish, document, implement and maintain an asset management system and continuously improve their efficiency; in addition to define the scope of asset management system, raising objectives and measurable and achievable strategies. The route for the implementation of proper Asset Management System is to run the pillars of TPM, as a management strategy allows for an organized system by establishing a methodology which tends to eliminate the interruptions and interferences in the production process, optimizing and maximizing management of equipment and men, creating a strategy to measure the competitive capabilities through rigorous elimination of the deficiency of operating systems, making a difference in the organization related to its competition, improving response times, reliability of supplies, the knowledge that people have and the quality of final products and services.